A study on online consumer behaviour of impulsive buying and online consumer satisfaction during festival season in Malaysia among of UTAR student - Ng, Jia Qi (2023)
The rise of e-commerce brings along the rise of online consumers' online shopping culture. In addition, online consumers will impulse buy during the festive season, especially since Malaysia has various festive seasons. The satisfaction of online consumers is also important because retailers need to build customer loyalty and provide suitable promotions to encourage impulse buying. This study aims to analyse online consumer behaviour and identify online consumer satisfaction during the festive season in Malaysia by using Hawkins Stern’s impulsive buying theory. The research uses quantitative survey questionnaires as methodology; non-probability sampling will be applied in the survey with 50 respondents. All of the data will be analysed using descriptive statistics to test the research objectives and hypotheses. The findings have shown that consumers planned impulse buying during the festive season, and there are eternal factors such as promotions and service quality that may influence their buying decision and their satisfaction with the buying experience. With this study, marketers, consumers, and researchers in the future will have a deeper understanding of online consumer behaviour in Malaysia and how to ensure the satisfaction of online consumers.